Adjuvant trials for pancreatic cancer: where are we going and what is needed?. (May 2011) - Russo, Suzanne; Ove, Roger; Contreras, Carlo; Saif, Muhammad Wasif
The prognosis for pancreatic cancer remains poor and curative treatment currently involves multimodality therapy including resection. Effective systemic therapy regimens with or without radiation are needed; however, an optimal treatment paradigm is not clearly defined. Adjuvant therapy clinical trials are evaluating the potential benefit of targeted agents and the addition of radiation to systemic chemotherapy. Neoadjuvant treatments are also under investigation for resectable and borderline/potentially resectable tumors. Additional study goals include identification of patients at risk for pancreatic cancer and improvements in prediction and prognostication, which may lead to personalized treatment strategies. This article reviews data for neoadjuvant and adjuvant treatment for localized pancreatic adenocarcinoma and provides insight into the future evolution of treatment for patients with this deadly disease.